Poláritons magnéticos em meio giromagnético com camada de grafeno - Dantas, Leonardo de Queiroz (2021)
In this work we present the theoretical study on magnetic polaritons (magnon-polaritons) in a system formed by a semi-infinite gyromagnetic medium (ferromagnetic or antiferromagnetic), with a layer of graphene at the interface between this medium and the vacuum. Thus, the analytical and numerical calculations were reviewed for cases in which a static magnetic field is applied parallel to the interface, and we propose a new case, in which the magnetic field is applied perpendicularly to the interface between the media. The results found show that, for the case of perpendicular magnetic field, there was the formation of magnetic surface polariton modes, characterizing the photon-magnon coupling. In this case, the numerical results showed that these modes propagate reciprocally, that is, independent of the direction of the wave vector for both magnetic media (ferromagnetic and antiferromagnetic). In contrast, bulk modes were not found, characterizing an independent behavior between photon and magnon in the gyromagnetic bulk. The inclusion of the graphene layer also made it possible to control the surface modes by varying the parameters existing in the optical conductivity in graphene, such as the chemical potential and the scattering rate.